Communication in Organization - Wahyuni, Indah; Hayati, Fitri (Indikator Pendidikan Indonesia, 2022)
Organizations and groups depend on effective communication to perform all functions, including planning, directing, controlling, making decisions, and implementing decisions and goals. In addition, communication is at the heart of the organizational building. In an organization, communication is a tool that functions as a liaison and generator of motivation between each member of the organization so that an organization can move forward according to organizational goals. Ineffective communication and miss communication generate most of the organizational problems such as conflicts, disputes, prejudice, wrong decisions, poor execution, gaps and misunderstandings. Therefore, effective communication is paramount for the success of any organization, the basic elements of effective communication are clear thinking, clear speaking, clear writing, and these must be remembered as these are very basic.